Poultry protein hydrolysates in diets for tilapia fingerlings (Research, Society and Development, 2021)
The present study aimed to evaluate parameters of productive performance of Nile tilapia fingerlings fed with diets containing levels of hydrolyzed chicken protein (PHF). A total of 420 animals with an average weight of 1.8 ± 0.7 g were used, distributed in a completely randomized design with seven treatments and four replications. The animals were placed in 28 tanks of 70 L of useful volume with artificial aeration using an air blower. Seven diets were prepared, one control ration and another six rations with increasing levels of inclusion of hydrolyzed chicken protein (0, 1, 2, 3, 4, 5 and 6%). The animals were fed six times a day for 30 days and, at the end of the experimental period, weight and total length measurements were taken for later calculation of production parameters, in addition to the collection of biological material for histology. Data were subjected to analysis of variance (ANOVA) and polynomial regression analysis at 5% probability. Quadratic effects (p0.05) the total length, survival and muscle, liver and intestine morphometry of fingerlings. The inclusion of PHF did not affect the productive performance of Nile tilapia fingerlings at levels of up to 6% of this product in the diets. Therefore, it is recommended to use 3% of PHF for better weight gain of animals.